Analisis Motivasi Kerja Dan Kompetensi Manajerial Kepala Sekolah Terhadap Disiplin Kerja Guru (Studi di SMP Negri 02 Kota Blitar) - Ema Prasetyorini (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The purposes of the study were (1) explain the influence job motivation to teachers performance, (2) explain the influence headmaster managerial competences on teachers performance, (3)explain the influence job motivation and headmaster managerial competences on teachers performance of Junior High School 02 Blitar. Respondent in this research are 85 teachers. The results of data analysis proves that (1)there is influence of job motivation on teachers performance , (2)there is influence of headmaster managerial competenceson performance, (3)there is influence of job motivation and headmaster managerial competences on teachers performance. Thus, job motivation, headmaster managerial competences, and teachers performance has a big influence on teachers performance, that has become necessity for personnel of education to always pay attention and improve the job motivation and headmaster managerial competences to improve the teachers performance without forgetting the other factors that influences on teachers performance.